Variation of Jargon in Naposo Nauli Bulung Group Batak Angkola Society - Ira Fauziah Sitompul; Morada Tetty; Elisa Betty Manullang (Universitas Negeri Medan, 2020)
This study was focused on Jargon used byNaposo Nauli Bulung group in Batak Angkola society. The objectives of this study were to find out kinds of Jargons used inNaposo Nauli Bulung group, and to describe the meanings of jargons related to denotative and connotative meaning. This study was conducted by using descriptive qualitative method. The data were taken from the interpersonal functions of Naposo Nauli Bulung group in Batak Angkola societyand gathered descriptively, where the data is obtained, analyzed, classified and interpreted based on the results of research in the field. The technique used in the study was a technique documentary communication by Bailey (1994). The findings of this study show that kinds of jargon used in Naposo Nauli Bulung group classified into seven categories, namely Basilect, Colloquial, Cant, Slang, Vulgar, Acrolect, Argot.There were 100jargons founds in Naposo Nauli Bulung group, 63 jargon (63%) has denotative meaning and 37 jargon (37%) has connotative meaning. Base on the result, jargon was the most frequent that occurred among group members.